Metode Dakwah Islam dalam Menanamkan Pemahaman Agama Bagi Siswa Tunagrahita di SLB YPAC Medan Timur - Yosiyana, Kharisma; Soiman (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to find out and explain the method of Islamic da'wah in instilling religious understanding for mentally retarded students. This research method uses descriptive qualitative. In data collection techniques, this research uses interviews and observation. The results of the research show that the da'wah method applied by SLB YPAC to students with mental retardation is the method contained in the Al-Quran Surah An-Nahl verse 125 such as: Bil-Hikmah, namely with an approach to children with mental retardation by reading the situation or mood condition. the honey. Mauizah Hasanah is giving good advice, with good words, not by forcing Bil-Qalam, namely preaching through writings or other media that is easy to understand and attracts the attention of lay and educated circles. In conveying the message at SLB YPAC, it uses animated video media where in the video there are prayer practice movements, sholawatan using rhythms such as singing, reading short letters, reading daily prayers, getting to know the hijaiyah letters and also getting to know the Asmaul Husna. Da'wah actors use these animated videos to attract the attention and enthusiasm of mentally retarded children so they want to follow the movements and words in the animated videos. This activity is held every Friday, called Religious Friday. With this method you can. accepted by mentally retarded students and can be implemented into everyday life.